Pengaruh Disiplin Kerja Dan Motivasi Terhadap Kinerja Karyawan Pada PT.Mercu Buana Center Meruya Jakarta Barat - Andi, Dede; Andika, Dwi (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of work motivation and work discipline on the performance of employees of the Security Section of PT Mercu Buana Center Meruya, West Jakarta. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of 52 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are that work motivation has a significant effect on employee performance with a determination coefficient value of 49.1% and the hypothesis test is obtained t count > t table or (6.945 > 2.009). Work discipline has a significant effect on employee performance with a determination coefficient value of 42.9% and hypothesis testing obtained t count > t table or (6.126 > 2.009). Work motivation and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 9.631 + 0.402X1 + 0.363X2. The coefficient of determination is 58.3% while the remaining 41.7% is influenced by other factors. Hypothesis testing obtained F count > F table or (34.298 > 2.790).